Shaping online learning communities and the way adaptiveness adds to the picture. (10th February 2005) - Markellou, Penelope; Rigou, Maria; Tsakalidis, Athanasios; Sirmakessis, Spiros
With learning being a process closely connected to sociability, learning on the web is in many cases accompanied and promoted by the creation and maintenance of online communities. Even though today's web-based learning environments have drastically evolved and now incorporate techniques from other domains and application areas (such as web mining, AI, user modelling, and profiling), setting up a successful online learning community is not a trivial task. Experience has indicated that the road from assuring all technical prerequisites to having people participating and keeping the community "alive", is long and winding. This paper argues that by monitoring the behaviour of community members, their expertise, skills, opinions and/or preferences and requirements and by applying certain adaptation mechanisms, the experience and effectiveness of online learning can be significantly improved.